Age‐related decline in divided‐attention: from theoretical lab research to practical real‐life situations. Issue 6 (30th September 2013) - Fraser, Sarah; Bherer, Louis
<x xml:space="preserve">Abstract</x> The purpose of this advanced review is to provide readers with an up‐to‐date synopsis of age‐related changes in divided‐attention abilities. An interdisciplinary approach is taken, supplying readers with evidence from very structured laboratory studies and findings from more ecological research studies that target real‐life divided‐attention situations (i.e., walking and talking). The review goes beyond the reported age‐related declines in divided‐attention abilities and offers the reader an overview of current cognitive (dual‐task) training findings which suggest that these declines can be diminished with training. The contents of this review and the future directions proposed demonstrate that divided‐attention research and its recent application to aging and mobility has become a major and fast growing scientific field of investigation. WIREs Cogn Sci 2013, 4:623–640. doi: 10.1002/wcs.1252 Conflict of interest: The authors have declared no conflicts of interest for this article. For further resources related to this article, please visit the WIREs website.